Evaluating the impact of a retail management programme on graduates’ industry readiness at a selected South African university - Tlapana, Tshepo; Ntobaki, Paballo Patience; Matli, Cleopatra Moipone (Central European Journal of Educational Research, 2025)
This study explored the effectiveness of a Retail Management Programme in preparing students for employment in the retail industry. In South Africa, there is growing concern about the disconnect between university education and the labour market's expectations. The primary aim of this study was to assess whether the programme provides students with the relevant skills and knowledge necessary for the workplace. A quantitative research method was employed, and data was collected through questionnaires completed by 40 retail management students. The responses were analysed using descriptive and inferential statistics with the Statistical Package for Social Sciences (SPSS). The findings indicate that most students felt well-prepared for customer service, digital work tools, and retail operations. However, some students expressed uncertainty about their readiness, particularly in areas such as data analysis and decision-making. Students were primarily motivated to enroll in the programme to acquire transferable skills and enhance their employment prospects. They also valued training that mirrored real work environments. The study recommends incorporating more input from industry professionals, utilising greater practical learning methods, and placing a stronger emphasis on soft skills, including communication, teamwork, and problem-solving. Additionally, curriculum updates and improvements to career support services are suggested to facilitate a smoother transition for students into the job market.